Peru facing its bicentennial: Social imaginaries in colonial resistance against the popular decision - Alvarez Chávez, Roland (2021)
This article is created in the framework of the second-round presidential elections in Peru, from the narrative that has been generated during the political campaign and the reactions that have been seen in the media and on social networks, once that the results of the quick count were known, and they resulted in a slight distance in favor of Pedro Castillo, candidate of Peru Libre political party. The analysis proposed comes from the social imaginaries approach, to locate and try to analyze a series of discourses that have been built on the figure of the candidate of Peru Libre, and that constitutes the reflection of a resistance process that can be interpreted as ‘colonial’, which has also placed the country in a political polarization context, facing our Bicentennial as a independent Republic. Categories such as communist, terrorist, poor and unprepared highlander, and enemy of development are the main conditions attributed to the candidate Castillo that will be described and analyzed in this space. Undoubtedly, this subject constitutes a key issue for the current reality of the country, since we are facing a problem that dates back a long time, and that apparently in all these years has been postponed. The last elections have demonstrated the need and demand for a change in ‘the system’, especially from the areas and citizens historically most excluded and marginalized in the country.